Pengungkapan Corporate Social Responsibility dan Nilai Perusahaan dengan Good Corporate Governance sebagai Pemoderasi - Yudiantari, I Gusti Ayu Novi; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 33 No 12 (2023)DO - 10.24843/EJA.2023.v33.i12.p07, 2023)
The purpose of study to obtain empirical evidence on the influence of Corporate Social Responsibility disclosure on firm value with Good Corporate Governance as a moderator. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The sample was determined used purposive sampling technique and obtained the number of samples used as objects of observation was 134 company data. The data analysis technique used is Moderate Regression Analysis (MRA). Based on the analysis conducted, the results were obtained that the Corporate Social Responsibility disclosure has a positive effect on firm value and Good Corporate Governance weakens the positive effect of Corporate Social Responsibility disclosure on firm value. Corporate Social Responsibility Disclosure; Good Corporate Governance; Firm Value